Impact of The use of Information Technology on the Effectiveness of the Internal Control System in Libyan Commercial Banks (Economic studies journal, 2020)
This study aims to know the impact of the use of information technology on the effectiveness of the internal control system in commercial banks in the Libyan city of Sirte by studying the following variables (software used, online banking and communications used), the study relied on the Descriptive Analytics method through the design of a questionnaire distributed to the sample of the study where included  all employees working in commercial banks in the city of Sirte. A number of statistical methods were used, the most important of which were (arithmetic mean, standard deviations, relative weight, degree of importance), Also the Cronbach's alpha to test the credibility of the data, Multiple Regression coefficient  And Pearson's correlation coefficient, The most important findings of the study: The existence of a significant moral impact of software used and  online banking services on the effectiveness of the internal control system in commercial banks.
Keywords: Technology - Information - Effectiveness - Internal Control – Banks